Commentary on Plato's Gorgias - Olympiodorus, the Younger, of Alexandria, active 6th century. (Philosophia Antiqua, 1998)
This book provides a translation of the only surving ancient commentary on Plato's Goroias , written by the Alexandrian Platonist Olympiodorus in the sixth century A.D. There are substantial notes on the commentary, which assist the reader to understand the context of Olympiodorus' Platonism, the choices available to him as an interpreter, and the special characteristics of his interpretation. A full introduction tackles the issues of greatest interest that arise from the work, including the author's mission as a Hellenist resisting Christian attacks on his discipline. Indices are provided. The authors show that there is much more of value in this commentary than has often been supposed, and that the differences between Olympiodorus' approach and those of modern commentators are often illuminating.